IMMUNOGLOBULIN LEVELS IN SERUM AND CERVICOVAGINAL SECRETIONS OF PATIENTS INFECTED WITH TRICHOMONAS VAGINALIS - Mushrif, Ekhlas; Al-Kuraishi, Azhar Hatif; Ad´ hiah, Ali H (Al-Nahrain Journal of Science, 2010)
Trichomoniasis caused by Trichomonas vaginalis, is one of the most commonsexually transmitted parasites in the world, accounting for approximately 170 millioninfections annually. Although the factor behinds such incidence is still not clear,local and systemic host immune response is involved.Objectives: Accordingly, the present research was planned to determine the level ofimmunoglobulins (IgA, IgG and IgM) in sera and vaginal washes of women infectedwith T. vaginalis.Materials and Methods: Fifteen women infected with T. vaginalis (culture confirmed) and15 healthy females were inspected for total level of IgA, IgG and IgM in their seraand vaginal washes by means of single radial immunodiffusion.Results: The total level of IgA, IgG and IgM in serum and vaginal wash of patients and controlsshowed no significant difference, with the exception of IgG, which showed asignificant increased mean in the sera of patients.Conclusion: Humoral immune response is important in controlling T. vaginalis, with a specialreference to IgG